Pseudocyst of the auricle in patients with movement disorders: report of two patients with ataxia-associated auricular pseudocysts - Bryce D. Beutler (Mattioli1885, 2015)
Background: Pseudocyst of the auricle is a benign condition of the ear characterized by an asymptomatic, noninflammatory swelling on the lateral or anterior surface of the auricle. It typically presents as a 1 to 5 centimeter cystic lesion located within the scaphoid or triangular fossa. In most patients, the lesion develops spontaneously. However, pseudocyst of the auricle has also been associated with trauma to the ear.